Design and performance analysis of digitally controlled multi-mode multi-band power amplifier for Sub-6 GHz applications - Ganesh Racha; K Lal Kishore; Yedukondalu Kamatham; Srinivasa Rao Perumalla (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
The user requirements for present real-time applications are addressed by using technology improvements to create portable User Equipment (UE) communications devices. This device helps to support multiple applications using different technology modes and frequency bands. This device is designed by using an RFFE with a Power Amplifier, LNA, Up/Down converters, etc. This paper deals with the design of Multi-Mode Multi-Band (MM-MB) PA using digital control logic to support technology modes of GSM, LTE, and LTE Wi-Fi. The Multi-Band frequencies to support Multi-Modes are 900 MHz, 1800 MHz, 2.4 GHz, and 5 GHz respectively for Sub-6 GHz (FR1) applications. The digital control logic is used to select the required mode and band as per the switching logic and the PA circuits are designed by using Class E with input matching, biasing, and tuning circuit using a matched load of 50 Ω impedance. All the designs are realized by using the Cadence Virtuoso environment and the performance metrics are evaluated using transient, Periodic Steady State, and Periodic S-Parameter analysis. The designed circuit at 900 MHz and 1800 MHz works with an output power of 17 mW, and 8 mW for an input power of 5 dBm respectively. The designed circuit at 2.4 GHz and 5 GHz works with a power of 37 mW, and 38 mW for an input power of 5 dBm respectively. All these PA circuits are digitally controlled to create MM-MB PA for Sub-6 GHz applications.